An expert system coupled with a hierarchical structure of fuzzy neural networks for fault diagnosis - Calado, Joao M.F.; Sá da Costa, Jose M.G. (Zielona Góra: Uniwersytet Zielonogórski)
An on-line fault diagnosis system, designed to be robust to the normal transient behaviour of the process, is described. The overall system consists of an expert system cascade with a hierarchical structure of fuzzy neural networks, corresponding to a multi-stage fault detection and isolation system.
Keywords: fault diagnosis; fault detection; fault isolation; expert system; fuzzy neural network; abrupt faults; incipient faults; shallow knowledge; deep knowledge